POTENSI PENGGUNAAN FERMENTASI TEPUNG DAUN KELOR (Moringa oleifera) SEBAGAI BAHAN BAKU PAKAN TERHADAP PERTUMBUHAN DAN SINTASAN BENIH IKAN MAS KOKI (Carrasius auratus) - Renanti, Tia; Komariyah, Siti; Febri, Suri Purnama; Nazlia, Suraiya; Aprita, Ika Rezvani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This research aims to determine the growth of goldfish fry treated with Moringa leaf flour in feed at different doses. The method used in this research was a Completely Randomized Design (CRD) with 4 treatments with 3 replications. In each treatment, doses of Moringa leaf flour were given P1=0% (control), P2=25%, P3=50%, and P4=75%. The results of this treatment had a significant effect on absolute weight growth, absolute length growth, and feed conversion. Meanwhile, the daily growth rate and survival rate had no effect. The highest daily growth rate was in P4 (75%) with a yield of 1.09%, while the lowest treatment was P2 (25%) and P3 (50%) with a yield of 0.97%. The highest absolute weight growth was in P4 (75%) with a yield of 1.29 g, while the lowest treatment was P1 (0%) and P2 (25%) with a yield of 1.06 g. The highest absolute length growth was in P4 (75%) with a result of 1.12 cm, while the lowest treatment result was P1 (0) with a result of 0.84 cm. The best feed conversion ratio at P4 (75%) with a yield of 1.59% was the best treatment among the other treatments. From the results of adding Moringa leaf flour at different doses to the feed, the higher the dose of Moringa leaf flour given, the resulting growth is in the better category. The results of the best survival were in the P4 treatment (75%) with a result of 96.66, which was the best treatment among the other treatments.